The effect of plasmids and other molecules on the effectivness of antibiofilm agents - Luciana Gomes (2014)
State-of-the-art contents on applied biofilm research from diagnosis to treatment of biofilm related disease Both bacterial and fungal biofilm issues are included With contributions by international experts This book provides a survey of recent advances in the development of antibiofilm agents for clinical and environmental applications. The fact that microbes exist in structured communities called biofilms has slowly become accepted within the medical community. We now know that over 80% of all infectious diseases are biofilm-related; however, significant challenges still lie in our ability to diagnose and treat these extremely recalcitrant infections. Written by experts from around the globe, this book offers a valuable resource for medical professionals seeking to treat biofilm-related disease, academic and industry researchers interested in drug discovery, and instructors who teach courses on microbial pathogenesis and medical microbiology.